Perlindungan Hukum terhadap Konsumen dalam Peredaran Barang yang Diproduksi Tidak Sesuai dengan Label - I Nyoman Gallan Tri Prasuta Purwanta; Ni Luh Made Mahendrawati; Ni Made Puspasutari Ujianti (Jurnal Konstruksi Hukum, 2021)
In this era, the growth of the goods and services industry has had a positive impact. One of the positive impacts is providing sufficient quantity and higher quality demand, as well as there are a lot of alternative choices for consumers to meet their needs. On the other hand, there are also negative impacts, namely the use of technology and the impact of business behavior due to increased competition which has an impact on the consumer community. This study aims to determine whether business actors are responsible for consumer losses related to goods that are not produced in accordance with the label, and to find out what legal sanctions have been imposed on business actors for violations due to inappropriate labels and manufactured goods. This type of research is normative legal research. The results show that the responsibility of commercial actors is related to the mismatch between the label and the goods produced, namely compensation for damage, pollution, and consumption of goods or services. Then, legal sanctions can be imposed for violations of business actors, including imprisonment for a maximum of 5 (five) years or a maximum fine of Rp. 2 billion. Thus, it can be concluded that business actors can be held accountable for the incompatibility of labels with goods that have been produced, and if the violation is too detrimental to consumers, they can be prosecuted in accordance with applicable laws and regulations.